PENGARUH RASIO AKTIVITAS DENGAN PERHITUNGAN PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2023 - Aulia, Siti Zahra; Santoso, Budi (Jurnal Nusa Akuntansi, 2025)
The pharmaceutical industry is a crucial sector in Indonesia's economy. The profitability of pharmaceutical companies is key to their sustainability and business development. One of the factors that influences profitability is the efficiency of company asset management, which can be measured from cash turnover, receivables turnover and inventory turnover. The aim of this research is to determine and analyze the effect of cash turnover, accounts receivable turnover and inventory turnover on profitability in Pharmaceutical Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2014-2023. The data used in this research consists of secondary data from financial statements for the years 2014-2023. This research used purposive sampling to obtain a sample of 6 companies. The analysis technique in this research uses descriptive analysis, panel data regression analysis, classical assumption testing, and hypotheses. The research results show that partially the cash turnover and receivables turnover variables do not have a significant effect on profitability, while receivables turnover has a significant effect on profitability. simultaneously the variables cash turnover, accounts receivable turnover and inventory turnover have a significant effect on profitability.